2D electrostatic modeling of twisted pairs. Issue 1 (2nd December 2021) - Hazim, Kaoutar; Parent, Guillaume; Duchesne, Stéphane; Nicolet, Andrè; Geuzaine, Christophe
Abstract : Purpose: This paper aims to model a three-dimensional twisted geometry of a twisted pair studied in an electrostatic approximation using only two-dimensional (2D) finite elements. Design/methodology/approach: The proposed method is based on the reformulation of the weak formulation of the electrostatics problem to deal with twisted geometries only in 2D. Findings: The method is based on a change of coordinates and enables a faster computational time as well as a high accuracy. Originality/value: The effectiveness of the adopted approach is demonstrated by studying different configurations related to the IEC 60851-5 standard defined for the measurement of the electrical properties of the insulation of the winding wires used in electrical machines.